Antibiotic Resistance Study and Detection of Virulence Gene among Uropathogenic E.coli - Zhian g. nanakali; Zirak F. Ahmad (Kirkuk Journal of Science, 2015)
A total of two hundred and fourteen outpatient and inpatient children their ages ranged from 1day to 14 years, whether symptomatic or asymptomatic were studied for urinary tract infections (UTIs) during the period (February to May 2012) at Rapareen Teaching Hospital for Children in Erbil City. Urine samples were collected and examined using microscopic, dipstick test for detection of leukocyte esterase and culture techniques. Isolated organisms were identified using microscopical, morphological and biochemical tests (including recent Vitek 2 system) and the results showed that positive urine cultures were detected in 134 (62.6 %) children, among females were 98 (73 %), while among males were 36 (27 %). Microorganisms that had been isolated from urine culture were mainly Escherichia coli 70 (52.2 %) followed by others. The isolates appeared to be varied in their resistance to antibiotics, and the highest resistance were for ampicillin 67 (95.7 %), while the most effective antibiotic used was imipenem .Total E.coli isolates also tested for their ability to produce hemolysin and the results showed that 27 (38.5%) were α-hemolysin, 9 (12.8%) β-hemolysin and 34(48.5%) were γ-hemolysin producers.. Out of 70 Escherichia coli isolates, 41 (58.5%) were found to be ESBLs producers, while 29 (41.4%) were non ESBLs producers. The plasmid profile of studied E.coli isolates revealed that plasmids were found in 64 (91.6%) of isolates with different molecular weights ranged from 1- more than10 kbp. Curing of plasmid DNA content were conducted using sodium dodecyl sulfate (SDS) and elevated temperature at 46Co. The results revealed that the curing percentage for isolate E3 was (50%) while for isolate E25 was (41.6%) for antibiotics understudy. On the other hand these two isolates when incubated at 46 Co the curing percentage were (66.6%) and (58.3%) respectively. Also the cured colonies tested for their ability to produce ESBLs and the results demonstrated that the cured colonies cannot produce ESBL indicating that the genes responsible for this trait are plasmid situated.Among 70 UPEC isolates, 61(87.1%) UPEC were positive for the existance of aerobactin virulence gene using PCR.